Review of Neurosystasis Satchell, with two new species from Cuba and a discussion of cerci and surstyli in Psychodinae (Diptera: Psychodidae) - Kvifte, Gunnar Mikalsen; Wagner, Rüdiger (Zootaxa, 2017)
Two new species, Neurosystasis mira Wagner & Kvifte, sp. nov., and Neurosystasis starki Wagner, sp. nov. are described and illustrated based on male specimens from Cuba. The new species are placed in context within the genus through a review of the biology, morphology and diversity of the genus. A revised generic diagnosis is presented to correct earlier diagnoses, and the genus Chuspilepia Omad, Mangudo & Gleiser, 2015 is placed as a subjective synonym of Neurosystasis, syn. nov.. The term hypopod is proposed to refer to the posterior genitalic appendages of Psychodinae, which in the literature have been treated both as surstyli (i.e. from the epandrium, 9th segment), cercopodia (i.e. from the proctiger, 10th segment) or a combination of both. Tentative evidence is presented for the hypopods of Neurosystasis comprising a mesal branch deriving from cerci and a lateral branch deriving from surstyli. A key is presented for identification of males of world Neurosystasis species.